Densification of Magnesium Aluminate Spinel Using Manganese and Cobalt Fluoride as Sintering Aids - Talimian, Ali; Pouchly, Vaclav; Maca, Karel; Galusek, Dusan (Materials (Basel, Switzerland), 2019)
Highly dense magnesium aluminate spinel bodies are usually fabricated using pressure-assisted methods, such as spark plasma sintering (SPS), in the presence of lithium fluoride as a sintering aid. The present work investigates whether the addition of transition metal fluorides promotes the sintering of MgAl2O4 bodies during SPS. At the same time, such fluorides can act as a source of optically active dopants. A commercial MgAl2O4 was mixed with 0.5 wt% of LiF, MnF2, and CoF2 and, afterwards, consolidated using SPS at 1400 °C. Although MnF2 and CoF2 promote the densification as effectively as LiF, they cause significant grain growth.
Keywords: lithium fluoride; manganese fluoride; grain growth; cobalt fluoride; spark plasma sintering; MgAl2O4